Implementation of a control system of intelligent antennas based on the sequential quadratic programming (SQP) algorithm - Nemri, N.; Hammami, A.; Ghayoula, R.; Gharsallah, A.; Trabelsi, H.; Grenier, D. (The 8th European Conference on Antennas and Propagation (EuCAP 2014), 2014)
This paper describes a global electromagnetic optimization technique using SQP's method and apply it to guide the radiation pattern of linear antenna array in a certain direction, without any mechanical rotation or movement that is only by controlling the phase parameters of N equally spaced and symmetric elements. This paper investigates how the implementation on STM8 of the signal processing in hardware affects the performance of the adaptive array antenna.